Developing Unbiased Teacher Identity in Pluri-Accent Reality: Research-Based Classroom Activities - Červinková Poesová , Kristýna; Lancová , Klára (Research in Language, 2022)
In the current pilot report, we draw on and further develop our previous research examining pre-service teachers’ attitudes and beliefs about accents, in which we proposed a pedagogical intervention reflecting certain aspects of our research outcomes, mainly the positive trend of embracing one’s non-nativeness. A set of four classroom activities, namely Nativeness perception test, Four corners, Bank of experiences and Sociodynamic teacher, were incorporated into three different online graduate courses in the winter and summer semesters 2020/2021 at the Department of the English Language and Literature, Faculty of Education in Prague. The piloting process was partly replicated in face-to-face classes of the following academic year. The overarching goal was to raise awareness of accent variation, especially in such a linguistically homogenous country as the Czech Republic and cultivate future teachers’ ability to address accent-related issues confidently, objectively and sensitively. The subsequent scrutiny of participants’ recorded discussions, written and/or oral feedback, submitted tasks as well as teachers’ observations indicated increased awareness of accent variability and a raised level of pedagogical confidence in approaching accent in the classroom context. Particularly, the respondents proved to be highly creative when devising adequate and supportive reactions to imagined negative comments related to accents or preventing them by specifically designing their lesson plans. Furthermore, the pedagogical intervention was appraised by the participating graduate students in their reflective assessment one year later.